(3CQHYhf MOjkKG aj GdCMcGes - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s ((3GdeOQSI GdSdWGfjI GdcGedjI (B_ (3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg Gdehab dSdhc SHd QTOg GdMOjK GdChd Yf GHf YeQ QVi Gddg YfgeG bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd (B: ( (3dGjbHd Gddg UdGI HZjQ WghQ hdG UObI ef Zdhd (B) s
(3BNQgG (B:s
(3GdMOjK GdCQHYhf (B: (3Yf YGFTI QVi Gddg YfgG Yf QShd Gddg Udi Gddg Ydjg hSde bGd (B( (3dGJbWY jO GdSGQb EdG ai QHY OjfGQ aUGYOkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs